Uniaxial compression bearing capacity of bolted ball-cylinder joint. (15th March 2019) - Zeng, Qiang; Guo, Xiaonong; Huang, Zewei; Zong, Shaohan
Highlights: Finite element models of BBC joints were established and verified. The uniaxial compression bearing capacity of the BBC joint was defined. Influence factors on the ultimate load of BBC joints were studied. Formulae of the ultimate load of BBC joints were proposed. Abstract: Bolted ball-cylinder joint (BBC joint) is an innovative joint system applied in non-purlin spatial truss structures. According to the theoretical analysis, the fitting formulae of the uniaxial compression bearing capacity of the BBC joint were proposed in this paper. Experiments on 5 BBC joints were introduced briefly at first. The finite element (FE) models were established using ABAQUS and verified by the experimental results. The numerical and experimental results agreed well with each other in failure modes and load-displacement curves. Subsequently, parametric study was conducted to investigate the effects of the dimensions of hollow cylinder, rectangular tube and ribbed stiffener on the bearing capacity of the joint. Finally, the formulae to estimate the uniaxial compression bearing capacity of the BBC joint were obtained by means of regression analysis. And the increasing coefficients of bearing capacity were obtained on the basis of parametric study. The calculation results were verified against the experimental and numerical results. It is indicated that the practical calculation formulae can estimate the uniaxial compression bearing capacity accurately.